Synthesis, Characterization and Structural Studies on the Fe(III) and Co(III) Complexes of Butyl Biguanide - George, Abraham; C. Nair, Hema (Asian Journal of Chemistry, 2010)
Complexes of Fe(III) and Co(III) with butyl biguanide (buformin) have been prepared and characterized using elemental analysis, magnetic moment measurements, molar conductance measurements and infrared and electronic spectroscopic techniques. The magnetic moment values are indicative of a high spin octahedral complex for Fe(III) and a diamagnetic octahedral complex for Co(III). The electronic and IR spectrum of Fe(III) and Co(III) complexes are in conformity with the octahedral structure.